1995
DOI: 10.1172/jci118194
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and regulation of expression of the rat kidney urea transporter (rUT2).

Abstract: In mammals, urea is the predominant end-product of nitrogen metabolism and plays a central role in the urinaryconcentrating mechanism. Urea accumulation in the renal medulla is critical to the ability of the kidney to concentrate urine to an osmolality greater than systemic plasma. Regulation of urea excretion and accumulation in the renal medulla depends on the functional state of specialized phloretin-sensitive urea transporters. To study these transporters and their regulation of expression we isolated a cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
136
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(157 citation statements)
references
References 35 publications
20
136
1
Order By: Relevance
“…As expected for a vasopressin-regulated transporter, UT2 is localized in the inner medullary collecting ducts and probably in the descending thin limbs of Henle's loop [9], where it plays a central role in the establishment of a corticomedullary osmotic gradient. Two transcripts (4.0 and 2.9 kb) of a rat urea transporter (rUT2) were identified in the kidney [7].…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…As expected for a vasopressin-regulated transporter, UT2 is localized in the inner medullary collecting ducts and probably in the descending thin limbs of Henle's loop [9], where it plays a central role in the establishment of a corticomedullary osmotic gradient. Two transcripts (4.0 and 2.9 kb) of a rat urea transporter (rUT2) were identified in the kidney [7].…”
Section: Introductionsupporting
confidence: 57%
“…3), at the opposite of the UT2 transcript which was present in the rabbit colon [6]. Recently, it was reported that the rat UT2 transcript was undetectable in the colon and it was suggested that this may represent an adaptation towards the dietary protein consumed between herbivore (rabbit) and omnivore (rat) [7].…”
Section: Tissue Distribution Of Hutl L and Hut2 Mrnasmentioning
confidence: 99%
See 3 more Smart Citations